Characterization and Adsorption Studies of Carbon Nanotubes / Nanofibers for Methane Storage - Mohamed Danna, Abdulhamid Belal (2004)
Natural gas (NG), which contains about 95% methane is currently gaining global acceptance as fuel for combustion engines because it is environmentally friendly and clean, naturally abundant, and cheaper than gasoline or diesel. Upon combustion when compared to gasoline or diesel it emits much less carbon dioxide (a major greenhouse gas) as well as several other air pollutants. However, the biggest challenge facing NG use as fuel for the transport industries is its storage. Therefore, carbon nano-structures have been synthesised using a typical floating catalyst chemical vapour deposition (FC-CVD) in a horizontal tubular reactor, which was fabricated in the Department of Chemical & Environmental Engineering, University Putra Malaysia. Ferrocene was used as the catalyst (Fe) precursor, benzene as the carbon source, while a mixture of hydrogen and argon was used as the carrier gas for both ferrocene and benzene vapours. The temperatures for the synthesis were varied between 1000 to 12000C to produce four distinct nanostructures, which are carbon nanotubes (CNTs), nanofibers (CNFs), nanoparticles (CNPs) and nanoporous carbon bulky balls (CNPBs). Upon scanning with scanning electron microscope (SEM) and transmission electron microscope (TEM), the diameters of the carbon nanostructures obtained ranged from 2 to 100 nm. Further characterisation with Accelerated Surface Area and Porosimetry system (ASAP 2000), using liquid N2 (77 K) for the Brunaur- Emmett-Teller (BET) surface characterisation, the surface areas, pore sizes and micropore volumes were found to be in range of 5.06 to 69.2 m2/g, 6.4 to 225.4Å, and 8.03 x 10-4 to 13.7 x 10-3 cm3/g, respectively for 0.602g samples. All samples had hysteresis indicating mesopore condensation of N2 with highest amount adsorbed on CNTs. CNFs and CNPs indicated the different type of isotherm with methane according to the BDDT (Brunauer, Dening, Dening and Teller) classification. A very great size difference was seen between N2 and CH4 hysteresis, which was due to the molecular structure, solid-like and liquid-like phases proposed for CH4 adsorption in and on the carbon nanostructure, respectively. A remarkable storage capacity of methane was achieved with these particles with storage capacity of 5.35 cm3/g for CNTs, 1.48 cm3/g for CNFs, and 0.3651 cm3/g for CNPBs at room temperature and atmospheric pressure